Co-production system of hemicellulose and hard carbon material

Through the cogeneration system of hemicellulose and hard carbon materials, the problem of low energy and resource utilization rate of hard carbon materials prepared by biomass is solved, and the electrochemical performance and resource utilization efficiency of hard carbon materials are improved.

CN119819215AActive Publication Date: 2025-04-15CENT SOUTH UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411888976.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-15
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

In the prior art, biomass hard carbon materials have problems of low energy and resource utilization and high energy consumption, and bamboo-based hard carbon materials have too many pores and too large specific surface area, which affects their electrochemical properties.

Method used

A cogeneration system of hemicellulose and hard carbon materials is proposed. The pretreatment module removes hemicellulose from biomass, combines alkali treatment and neutralization treatment to improve the microstructure of the material, and thus improves the reversible capacity and electrochemical properties of the hard carbon materials.

Benefits of technology

The comprehensive utilization of biomass has been achieved, the resource conversion rate has been improved, and the electrochemical performance of hard carbon materials has been improved by removing hemicellulose, which has significantly improved the resource utilization efficiency and environmental protection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a co-production system of hemicellulose and a hard carbon material, and relates to the technical field of biomass resource utilization. The co-production system comprises: a pretreatment module used for heating reaction of a first mixture comprising a biomass raw material and an alkaline agent, and carrying out first solid-liquid separation to obtain a first solid phase and a first liquid phase; the hemicellulose extraction module is used for sequentially carrying out neutralization treatment and extraction treatment on the first liquid phase and carrying out second solid-liquid separation to obtain hemicellulose and a second liquid phase; and the carbonization module is used for carrying out carbonization treatment on the first solid phase to obtain the hard carbon material. The comprehensive utilization of the biomass is realized, the hemicellulose and the hard carbon material are co-produced through cascade energy driving, and good economic benefits and environmental protection performance are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomass resource utilization, and in particular to a co-production system of hemicellulose and hard carbon materials. Background Art

[0002] Biomass is the earliest renewable resource used by humans. It has a wide range of sources and is inexpensive, such as agricultural and forestry waste, plant residues, fruit shells, bamboo, etc. The hard carbon obtained by pyrolysis and carbonization of biomass contains a large number of defects and pores, and has a large reversible capacity of more than 300 mAhg −1 , showing excellent electrochemical properties, and is currently the hard carbon precursor with the most application prospects.

[0003] In the related technologies, the use of biomass to prepare hard carbon materials generally has the problems of low energy and resource utilization and high energy consumption. Bamboo is a high-quality biomass resource. Compared with hard carbon materials prepared from other biomass, bamboo-based hard carbon materials have a lower specific surface area, thus having a higher first coulombic efficiency (ICE); they are rich in heteroatoms (such as nitrogen, sulfur, oxygen, etc.) and various functional groups (such as carboxyl, phenolic hydroxyl, etc.), which can provide additional active sites for sodium ion storage. However, hard carbon materials prepared from bamboo have the disadvantages of too many pores, too large specific surface area, low reversible capacity, and poor electrochemical performance. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. The present invention provides a system for the co-production of hemicellulose and hard carbon materials.

[0005] The present invention also provides a method for co-producing hemicellulose and hard carbon materials.

[0006] The present invention also provides application of the above-mentioned cogeneration system or cogeneration method.

[0007] According to an energy-step-driven co-production system of hemicellulose and hard carbon materials according to a first aspect of the present invention, the co-production system comprises: A pretreatment module, used for heating a first mixture including a biomass raw material and an alkaline agent, performing a first solid-liquid separation, and obtaining a first solid phase and a first liquid phase; A hemicellulose extraction module, used for sequentially performing a neutralization treatment and an extraction treatment on the first liquid phase, and performing a second solid-liquid separation to obtain the hemicellulose and the second liquid phase; A carbonization module is used to perform carbonization treatment on the first solid phase to obtain the hard carbon material.

[0008] The cogeneration system according to the embodiment of the present invention has at least the following beneficial effects: The co-production system of the embodiment has a high resource conversion rate, realizes the comprehensive utilization of biomass, can co-produce hemicellulose (yield of 16% to 20%) and hard carbon materials (yield of 15% to 18%), and has good economic benefits. The coordination and energy mobility between different modules are good, and the overall production system has good flexibility and scalability.

[0009] In addition, due to the poor thermal stability of hemicellulose, hemicellulose is easily decomposed to produce gases such as CO2 during the carbonization process, which makes the prepared hard carbon material have too large specific surface area and too many pores, affecting its electrochemical performance. The co-production system of the embodiment removes hemicellulose in biomass through pretreatment, effectively improving the electrochemical properties of the hard carbon material such as reversible capacity.

[0010] According to some embodiments of the present invention, the cogeneration system also includes an energy supply module for collecting volatiles and heat generated by the carbonization module, and providing heat for at least one of the pretreatment module, the hemicellulose extraction module, and the carbonization module. As a result, the cogeneration system is not completely dependent on external energy input, can effectively recover the waste heat generated by the carbonization process, and make full use of the calorific value of volatiles (including combustible gas, tar, etc.) generated by biomass carbonization for heating other modules. The system is driven by the energy ladder, which reduces energy consumption and environmental pollution, significantly improves resource utilization efficiency and environmental protection performance, and realizes the clean, low-carbon, and efficient conversion of biomass resources such as bamboo.

[0011] According to some embodiments of the present invention, the pretreatment module comprises an alkali treatment unit and a first solid-liquid separation unit connected in sequence, the first solid-liquid separation unit having a first liquid phase outlet and a first solid phase outlet; The hemicellulose extraction module comprises a neutralization extraction unit, a second solid-liquid separation unit and a drying unit connected in sequence; the neutralization extraction unit is connected to the first liquid phase outlet; the second solid-liquid separation unit has a second liquid phase outlet and a second solid phase outlet; the drying unit is connected to the second solid phase outlet; The carbonization module comprises a carbonization device and a cooling transpose connected in sequence, and the carbonization device is connected to the first solid phase outlet; The energy supply module includes a heat exchange device and a combustion chamber. The heat exchange device is connected to the cooling device, the combustion chamber and at least one of the alkali treatment unit, the drying unit and the carbonization device; the combustion chamber is connected to the carbonization device.

[0012] According to some embodiments of the present invention, the first solid-liquid separation unit includes at least one of a plate and frame filter press, a belt filter press, and a centrifugal filter.

[0013] According to some embodiments of the present invention, the second solid-liquid separation unit includes at least one of a plate and frame filter press, a belt filter press, and a centrifugal filter.

[0014] According to some embodiments of the present invention, the carbonization device comprises a first carbonization unit and a second carbonization unit connected in sequence, and the first carbonization unit is connected to the first solid phase outlet; The cooling device comprises a first cooling unit and a second cooling unit connected in sequence to the second carbonization unit; The combustion chamber is in communication with the first carbonization unit and the second carbonization unit.

[0015] According to some embodiments of the present invention, the heat exchange device includes a first heat transfer device and a second heat transfer device; The first heat transfer device is connected to the second carbonization unit and the first cooling unit at the same time; The second heat transfer device is connected to the second cooling unit, the combustion chamber, and at least one of the alkali treatment unit and the drying unit.

[0016] According to some embodiments of the present invention, the first heat transfer device includes an evaporation portion and a condensation portion which are connected in sequence, the evaporation portion is connected to the first cooling unit, and the condensation portion is connected to the first carbonization unit.

[0017] According to some embodiments of the present invention, the first heat transfer device contains a heat transfer medium with phase change heat transfer effect. The evaporation part is adjacent to the first cooling unit to absorb the heat emitted by the first cooling unit; the condensation part is adjacent to the first carbonization unit to provide heat for the first carbonization unit.

[0018] According to some embodiments of the present invention, the gasification temperature of the heat transfer medium is lower than the surface temperature of the first cooling unit and higher than the temperature required by the second carbonization unit. The working temperature of the heat transfer medium is 400°C to 600°C. The working temperature of the heat transfer medium refers to the temperature range in which the heat transfer medium can effectively transfer heat.

[0019] According to some embodiments of the present invention, the heat transfer medium includes at least one of sodium, potassium, sodium-potassium alloy, sodium nitrate, potassium nitrate, sodium chloride, and potassium chloride.

[0020] According to some embodiments of the present invention, the second heat transfer device includes a heating zone and a heat exchange zone connected in sequence, the heat exchange zone is connected to the second cooling unit and the combustion chamber, and the heating zone is connected to at least one of the alkali treatment unit and the drying unit.

[0021] According to some embodiments of the present invention, the second heat transfer device contains heat transfer oil having a heat transfer function.

[0022] According to some embodiments of the present invention, the working temperature of the heat transfer oil is between 100° C. and 150° C. The working temperature of the heat transfer oil refers to a temperature range in which heat transfer can be performed stably, safely and effectively.

[0023] According to some embodiments of the present invention, the heat transfer oil is water, fluorinated liquid or organic heat transfer oil.

[0024] According to some embodiments of the present invention, the fluorinated liquid includes at least one of 3M™ Fluorinert™ liquid, Dynalene™ HF-100, Novec™ 649 Fluid, and Perfluorocyclohexane (PFCH).

[0025] According to some embodiments of the present invention, the organic heat-conducting oil includes at least one of silicon-based heat-conducting oil, biphenyl heat-conducting oil and biphenyl ether low-melting mixture type heat-conducting oil.

[0026] According to some embodiments of the present invention, the silicon-based thermal oil includes at least one of Dow Corning® 200 Fluid and fluorosilicone thermal oil.

[0027] According to some embodiments of the present invention, the biphenyl thermal oil includes Therminol® 66.

[0028] According to some embodiments of the present invention, the diphenyl ether low-melting mixture type heat transfer oil includes Therminol®55.

[0029] According to some embodiments of the present invention, the second heat transfer device further comprises a low-temperature heat transfer oil tank and a high-temperature heat transfer oil tank. The oil inlet of the high-temperature heat transfer oil tank is connected to the oil outlet of the heat exchange zone, and the oil outlet of the high-temperature heat transfer oil tank is connected to the oil inlet of the heating zone, for storing high-temperature heat transfer oil; the oil inlet of the low-temperature heat transfer oil tank is connected to the oil outlet of the heat exchange zone, and the oil outlet of the low-temperature heat transfer oil tank is connected to the oil inlet of the heating zone, for storing low-temperature heat transfer oil after heat exchange.

[0030] According to some embodiments of the present invention, the co-production system further comprises a control module. The control module is used for real-time monitoring, data feedback and intelligent optimization. For example, sensors can be used to monitor the temperature, atmosphere changes and reaction progress in the carbonization module, and machine learning algorithms can be used to adjust process parameters in real time to improve production efficiency and product consistency.

[0031] According to the second aspect of the present invention, the method for co-producing hemicellulose and hard carbon materials comprises the following steps: Heat a first mixture including a biomass raw material and an alkaline agent to react, perform a first solid-liquid separation, and obtain a first solid phase and a first liquid phase; The first liquid phase is sequentially subjected to a neutralization treatment and an extraction treatment, and a second solid-liquid separation is performed to obtain the hemicellulose and the second liquid phase; the first solid phase is carbonized to obtain the hard carbon material.

[0032] The cogeneration method according to the embodiment of the present invention has at least the following beneficial effects: The co-production method of the embodiment removes hemicellulose in the biomass raw material through alkali treatment, and further shapes the microstructure of the material in combination with neutralization treatment, thereby increasing the porosity of the bamboo material and facilitating the deintercalation of sodium ions. If alkali treatment is performed after neutralization treatment, hemicellulose may be decomposed under acid treatment, and alkali treatment cannot effectively extract hemicellulose, which greatly reduces the resource utilization rate of the biomass raw material.

[0033] According to some embodiments of the present invention, the cogeneration method is performed in the cogeneration system described in the embodiment of the first aspect.

[0034] According to some embodiments of the present invention, the biomass raw material includes at least one of bamboo, wood, corn cobs, peanut shells, and coconut shells.

[0035] According to some embodiments of the present invention, the biomass raw material is bamboo.

[0036] According to some embodiments of the present invention, the particle size of the biomass raw material is 150 mesh to 300 mesh.

[0037] According to some embodiments of the present invention, the reaction time of the heating reaction is 1 h to 2 h. For example, it can be 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2 h.

[0038] According to some embodiments of the present invention, the reaction temperature of the heating reaction is 70°C to 90°C. For example, it can be 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C.

[0039] According to some embodiments of the present invention, the pH of the first mixture is 13-14. For example, it can be 13, 13.1, 13.2, 13.4, 13.5, 13.6, 13.7, 13.8, 13.9 or 14.

[0040] According to some embodiments of the present invention, the alkaline agent comprises an alkaline compound.

[0041] According to some embodiments of the present invention, the alkaline compound includes at least one of NaOH, KOH, and Ca(OH)2.

[0042] According to some embodiments of the present invention, the concentration of the alkaline compound in the alkaline agent is 3 wt.% to 10 wt.%. For example, it may be 3 wt.%, 3.5 wt.%, 4 wt.%, 4.5 wt.%, 5 wt.%, 5.5 wt.%, 6 wt.%, 6.5 wt.%, 7 wt.%, 7.5 wt.%, 8 wt.%, 8.5 wt.%, 9 wt.%, 9.5 wt.% or 10 wt.%.

[0043] According to some embodiments of the present invention, the solvent of the alkaline agent includes water.

[0044] According to some embodiments of the present invention, the solid-liquid ratio of the biomass raw material to the alkaline agent is 1 kg: (10-20) L. For example, it can be 1 kg: 10 L, 1 kg: 10.5 L, 1 kg: 11 L, 1 kg: 11.5 L, 1 kg: 12 L, 1 kg: 12.5 L, 1 kg: 13 L, 1 kg: 13.5 L, 1 kg: 14 L, 1 kg: 14.5 L, 1 kg: 15 L, 1 kg: 15.5 L, 1kg: 16 L, 1 kg: 16.5 L, 1 kg: 17 L, 1 kg: 17.5 L, 1 kg: 18 L, 1 kg: 18.5 L, 1 kg: 19 L, 1kg: 19.5 or 1 kg: 20 L.

[0045] According to some embodiments of the present invention, the first mixture also includes a dissolution aid solvent, which can be used to assist in dissolving the biomass raw material (such as bamboo powder).

[0046] According to some embodiments of the present invention, the dissolution aid includes at least one of water and ammonia water. The concentration of ammonia water is 2wt.%-8wt.%. For example: According to some embodiments of the present invention, the neutralization treatment comprises adjusting the pH of the first liquid phase to 2 to 6. For example, the pH may be 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.6, 3.8, 4, 4.2, 4.4, 4.6, 4.8, 5, 5.2, 5.4, 5.6, 5.8 or 6.

[0047] According to some embodiments of the present invention, the neutralization treatment uses a neutralizing liquid to adjust the pH of the first liquid phase.

[0048] According to some embodiments of the present invention, the neutralizing solution is an aqueous solution including at least one of an inorganic acid and an organic acid.

[0049] According to some embodiments of the present invention, the inorganic acid includes at least one of hydrochloric acid, phosphoric acid, hydrobromic acid, and sulfurous acid.

[0050] According to some embodiments of the present invention, the organic acid includes at least one of acetic acid, oxalic acid, citric acid, lactic acid, and formic acid.

[0051] According to some embodiments of the present invention, in the neutralization solution, the concentration of the inorganic acid is 6wt.% to 8wt.%. For example, it may be 6wt.%, 6.1wt.%, 6.2wt.%, 6.3wt.%, 6.4wt.%, 6.5wt.%, 6.6wt.%, 6.7wt.%, 6.8wt.%, 6.9wt.%, 7wt.%, 7.1wt.%, 7.2wt.%, 7.3wt.%, 7.4wt.%, 7.5wt.%, 7.6wt.%, 7.7wt.%, 7.8wt.%, 7.9wt.% or 8wt.%.

[0052] According to some embodiments of the present invention, the extraction process comprises: preparing a second mixture of the neutralized first liquid phase and a precipitant, and reacting.

[0053] According to some embodiments of the present invention, the volume ratio of the precipitant to the first liquid phase is (2-3): 1. For example, it can be 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1 or 3:1.

[0054] According to some embodiments of the invention, the precipitating agent comprises a poor solvent for hemicellulose.

[0055] According to some embodiments of the present invention, the precipitant includes at least one of an organic alcohol aqueous solution with a volume fraction of 60% to 80% and an acetone aqueous solution with a volume fraction of not less than 90%.

[0056] According to some embodiments of the present invention, the organic alcohol includes at least one of ethanol and ethylene glycol.

[0057] According to some embodiments of the present invention, the reaction time of the extraction treatment is 10 min to 30 min. For example, it can be 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min or 30 min.

[0058] According to some embodiments of the present invention, the carbonization treatment includes subjecting the first solid phase to a first carbonization treatment at 400°C to 600°C and a second carbonization treatment at 1000°C to 1500°C. The first carbonization treatment removes unstable chemical components (such as moisture, volatiles, and some organic matter) to obtain primary carbon; the second carbonization treatment further decomposes the organic matter in the primary carbon into a solid of almost pure carbon, while forming a specific microstructure. Combined with the secondary carbonization treatment, the microstructures of the hard carbon material, such as the pores and graphite microcrystalline layers, are effectively regulated, effectively improving its electrochemical properties, such as specific capacity and cycle stability.

[0059] According to some embodiments of the present invention, the treatment time of the first carbonization treatment is 0.5 h to 1.5 h. For example, it can be 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h or 1.5 h.

[0060] According to some embodiments of the present invention, the treatment time of the second carbonization treatment is 1 h to 2 h. For example, it can be 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2 h.

[0061] According to some embodiments of the present invention, the co-production method further includes a post-carbonization cooling process. The post-carbonization cooling process includes a first cooling process and a second cooling process; the cooling final temperature of the first cooling process is 500°C to 600°C; the cooling final temperature of the second cooling process is 80°C to 100°C.

[0062] According to some embodiments of the present invention, the first solid-liquid separation and the second solid-liquid separation are independently selected from centrifugation, filter pressing, and filtration.

[0063] According to some embodiments of the present invention, the co-production method further comprises: drying the hemicellulose.

[0064] According to the third aspect of the present invention, the co-production system as described in the second aspect or the co-production method as described in the second aspect is used in the preparation of hemicellulose, hard carbon materials, negative electrodes or secondary batteries.

[0065] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1Representative photos of hemicellulose solid and hard carbon material prepared in Example 1; wherein, (a) hemicellulose solid, (b) hard carbon material; Figure 2 This is a schematic diagram of a system for co-producing hemicellulose and hard carbon materials according to Example 1 of the present invention; Figure 3 These are SEM images of the hard carbon materials obtained in Example 1 and Comparative Examples 1-2; wherein (a) and (c) are AC, (b) and (e) are C, and (c) and (f) are DC; Figure 4 The XRD patterns of the hard carbon materials obtained in Example 1 and Comparative Examples 1-2 are shown below; Figure 5 The Raman spectra of the hard carbon materials obtained in Example 1 and Comparative Examples 1-2; Figure 6 N2 adsorption-desorption curves of the hard carbon materials prepared in Example 1 and Comparative Examples 1-2; Figure 7 The adsorption pore size distribution diagram of the hard carbon materials prepared in Example 1 and Comparative Examples 1-2; Figure 8 The desorption pore size distribution diagram of the hard carbon materials prepared in Example 1 and Comparative Examples 1-2; Fig. 9 The pore characteristics of the hard carbon materials obtained in Example 1 and Comparative Examples 1-2; Fig.10 The first cycle charge and discharge curves of the hard carbon materials prepared in Example 1 and Comparative Examples 1-2; Fig.11 Long cycle test of the hard carbon materials prepared in Example 1 and Comparative Examples 1-2; Fig.12 The rate performance test of the hard carbon materials prepared in Example 1 and Comparative Examples 1-2; Fig.13 The reversible capacity distribution of the hard carbon materials obtained in Example 1 and Comparative Examples 1-2; Fig.14 The electrochemical impedance spectra of the hard carbon materials prepared in Example 1 and Comparative Examples 1-2 are shown; Fig.15 The cyclic voltammetry test results of the hard carbon materials prepared in Example 1 and Comparative Examples 1-2 are shown in FIG. 1 , wherein (a) is AC, (b) is DC, and (c) is DC. Fig.16 Schematic diagram of energy flow of the co-production system of hemicellulose and hard carbon materials of the present invention. DETAILED DESCRIPTION

[0067] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0068] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0069] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0070] In the description of the present invention, it should be understood that descriptions involving orientation, such as orientation or positional relationship indicated as up, down, etc., are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0071] In the description of the present invention, it should be noted that, unless otherwise clearly defined, terms such as setting and connecting should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention in combination with the specific content of the technical solution.

[0072] In the description of the present invention, the terms "comprises" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatuses.

[0073] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0074] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0075] In the description of the present invention, primary charcoal yield = primary charcoal mass / bamboo powder raw material mass; Hard carbon material yield = hard carbon material mass / bamboo powder raw material mass; Hemicellulose yield = hemicellulose product mass / bamboo powder raw material mass.

[0076] In the embodiment of the present invention, the biomass raw material used is bamboo powder with a particle size of 150-300 mesh after being crushed and dried.

[0077] Example 1 This example provides a method for co-producing hemicellulose and hard carbon materials, the steps are as follows: S1. Mix 15 g of bamboo powder and 225 g of alkaline agent (3 wt.% NaOH aqueous solution) (the pH of the mixture is 0.35), and react at 80°C for 2 h to obtain a solid-liquid mixture; filter the solid-liquid mixture to separate the hemicellulose primary filtrate and the hemicellulose-free bamboo powder.

[0078] S2. Treatment of hemicellulose-removed bamboo powder: The hemicellulose-removed bamboo powder was treated at 500°C for 1 h, and primary carbon was obtained after cooling to room temperature (the primary carbon yield was 19%). The primary carbon was further carbonized at 1300°C for 2 h, and hard carbon material was obtained after cooling (denoted as: AC, the hard carbon material yield was 17%).

[0079] Treatment of hemicellulose primary filtrate: Add an appropriate amount of neutralizing liquid (6 wt.% dilute hydrochloric acid aqueous solution) to the hemicellulose primary filtrate to adjust the pH of the hemicellulose primary filtrate to 4.5, then add a precipitant (60 (V / V)% ethanol aqueous solution) 3 times the volume of the hemicellulose primary filtrate, and react for 1.5 hours to extract the hemicellulose in the hemicellulose primary filtrate to obtain a hemicellulose secondary suspension. The hemicellulose secondary suspension is centrifuged to separate the filtrate and the hemicellulose filter cake. The hemicellulose filter cake is dried in a drying device to obtain a hemicellulose solid (hemicellulose yield is 18%).

[0080] Representative photos of the prepared hard carbon materials and hemicellulose solids are shown in Figure 1 shown.

[0081] This example also provides a system for co-producing hemicellulose and hard carbon materials, which is used to implement the method for co-producing hemicellulose and hard carbon materials. Figure 2The co-production system consists of a pretreatment module, a hemicellulose extraction module, a carbonization module, and an energy supply module; the pretreatment module is connected to the hemicellulose extraction module in sequence; the pretreatment module is connected to the carbonization module in sequence; the energy supply module is used to collect volatiles generated by the carbonization module, absorb heat energy generated by the carbonization module, and provide heat energy for the pretreatment module, hemicellulose extraction module, and carbonization module.

[0082] (1) Pretreatment module: used for heating reaction of a first mixture including biomass raw materials and alkaline reagent, performing a first solid-liquid separation, and obtaining a first solid phase and a first liquid phase.

[0083] The pretreatment module consists of an alkali treatment unit (pretreatment device, which is a reactor with a stirring device and a jacket) and a first solid-liquid separation unit (plate and frame filter press) connected in sequence; the first solid-liquid separation unit has a first liquid phase outlet and a first solid phase outlet.

[0084] In the specific reaction, 15 g of bamboo powder and 225 mL of alkaline agent (3 wt.% NaOH aqueous solution) were added to the pretreatment device and reacted at 80°C for 2 h to obtain a solid-liquid mixture. The solid-liquid mixture entered the plate-and-frame filter press and was filtered to obtain the first liquid phase (hemicellulose primary filtrate) and the first solid phase (hemicellulose-free bamboo powder).

[0085] (2) Hemicellulose extraction module: used to perform a neutralization treatment and an extraction treatment on the first liquid phase in sequence, and perform a second solid-liquid separation to obtain a second solid phase (hemicellulose) and a second liquid phase.

[0086] The hemicellulose extraction module consists of a neutralization extraction unit (neutralization tank), a second solid-liquid separation unit (centrifugal filter), and a drying unit (drying device) which are connected in sequence; the neutralization extraction unit is connected to the first liquid phase outlet; the second solid-liquid separation unit has a second liquid phase outlet and a second solid phase outlet; and the drying unit is connected to the second solid phase outlet.

[0087] In the specific reaction, after the hemicellulose primary filtrate is transported to the neutralization tank, an appropriate amount of neutralizing liquid (6 wt.% dilute hydrochloric acid aqueous solution) is added to adjust the pH of the hemicellulose primary filtrate to 4.5, and then a precipitant (60 (V / V)% ethanol aqueous solution) with a volume of 3 times the hemicellulose primary filtrate is added to the neutralization tank and reacted for 20 minutes to obtain a hemicellulose secondary suspension. The hemicellulose secondary suspension enters a centrifugal filter for centrifugal treatment to separate the second liquid phase (filtrate) and the second solid phase (hemicellulose filter cake). The hemicellulose filter cake enters a drying device for drying to obtain a hemicellulose solid.

[0088] The filtrate can be stored in a filtrate tank to facilitate subsequent repeated treatment in a neutralization tank to extract possible residual hemicellulose.

[0089] (3) Carbonization module: used to carbonize the first solid phase to obtain a hard carbon material.

[0090] The carbonization module consists of a carbonization device and a cooling device connected in sequence; the carbonization device is connected to the first solid phase outlet. The carbonization device consists of a first carbonization unit (low-temperature carbonization furnace) and a second carbonization unit (high-temperature carbonization chamber) connected in sequence; the first carbonization unit is connected to the first solid phase outlet. The cooling device consists of a first cooling unit (primary cooling chamber) and a second cooling unit (secondary cooling chamber) connected in sequence to the second carbonization unit.

[0091] In the specific reaction, the high-temperature carbonization chamber is heated by an electric heating jacket. The high-temperature carbonization chamber, the primary cooling chamber, and the secondary cooling chamber are separated from each other by a grate and coaxially distributed longitudinally. A screw feeder is also provided between the low-temperature carbonization furnace and the vertical high-temperature carbonization furnace to transfer the material to the high-temperature carbonization chamber. The hemicellulose-removed bamboo powder enters the low-temperature carbonization furnace, is treated at 500°C for 1 h, and is cooled to room temperature to obtain primary charcoal (light volatiles are produced during the carbonization process). The primary charcoal is transferred to the high-temperature carbonization chamber by a screw feeder and carbonized at 1300°C for 2 h (heavy volatiles are produced during the carbonization process) to obtain secondary carbon. The secondary carbon falls to the primary cooling chamber through the grate and cools to 500°C~600°C; it continues to fall through the grate to the secondary cooling chamber and cools to 80°C~100°C to obtain a hard carbon material.

[0092] (4) Energy supply module: used to collect volatile matter and thermal energy generated by the carbonization module and provide heat for the pretreatment module, hemicellulose extraction module and carbonization module.

[0093] The energy supply module is composed of a heat exchange device and a combustion chamber; the combustion chamber is connected to the carbonization device. The heat exchange device is composed of a first heat transfer device and a second heat transfer device; the first heat transfer device is connected to the second carbonization unit and the first cooling unit at the same time; the second heat transfer device is connected to the second cooling unit, the combustion chamber, the alkali treatment unit, and the drying unit.

[0094] The combustion chamber is provided with a fuel inlet and an exhaust port. The combustion chamber is connected to the first carbonization unit and is used to collect light volatiles generated by the first carbonization unit; the combustion chamber is connected to the second carbonization unit and is used to collect heavy volatiles generated by the second carbonization unit. The combustion chamber generates heat by burning light volatiles, heavy volatiles, and fuel (the fuel can be biomass waste (such as bamboo powder waste such as bamboo branches that cannot be used for the preparation of hard carbon materials), and increases the temperature of the heat transfer oil in the second heat transfer device through heat exchange.

[0095] (4.1) First heat transfer device: The first heat transfer device (composite heat pipe, which has the characteristics of high thermal conductivity and stable operating temperature) is composed of an evaporation part (evaporation tube bundle) and a condensation part (condensation tube bundle) connected in sequence; the evaporation part and the condensation part form a loop; the evaporation part is connected to the first cooling unit to absorb the heat dissipated by the first cooling unit; the condensation part is connected to the first carbonization unit to provide heat to the first carbonization unit.

[0096] The first heat transfer device contains a heat transfer medium (potassium nitrate) with phase change heat transfer effect. In the specific working process, the heat transfer medium vaporizes after absorbing heat in the evaporation tube bundle, and is transferred to the condensation tube bundle driven by the pressure difference to condense, and the heat is thus transferred to the first carbonization unit. The condensed heat transfer medium can be circulated and transferred to the evaporation tube bundle through the capillary structure or gravity, thereby completing the transfer and exchange of heat. Those skilled in the art can achieve the desired temperature control by controlling parameters such as the diameter, length and medium flow rate of the composite heat pipe.

[0097] The first heat transfer device also includes a working medium storage tank, which is provided with a working medium inlet and a working medium outlet; the working medium inlet is connected to the condensation part, and the working medium outlet is connected to the evaporation part. It can be used to store heat transfer working medium.

[0098] (4.2) Second heat transfer device: The second heat transfer device (composite thermal oil heat exchange tube) is composed of a heating zone and a heat exchange zone connected in sequence; the heating zone and the heat exchange zone form a loop; the heat exchange zone is connected to the second cooling unit and the combustion chamber to absorb the heat emitted by the second cooling unit and the combustion chamber; the heating zone is connected to the alkali treatment unit and the drying unit to provide heat for the alkali treatment unit and the drying unit.

[0099] The composite heat transfer oil heat exchange tube contains heat transfer oil (Dow Corning® 200 Fluid) with heat transfer function. In the specific working process, the heat transfer oil absorbs heat in the heat exchange area and its temperature rises, which is then transferred to the heating area to provide heat for the alkali treatment unit and drying device. The heat transfer oil with lowered temperature is circulated back to the heating area, thus completing the heat transfer and exchange.

[0100] The second heat transfer device also includes a low-temperature thermal oil tank and a high-temperature thermal oil tank; the oil inlet of the high-temperature thermal oil tank is connected to the oil outlet of the heat exchange zone, and the oil outlet of the high-temperature thermal oil tank is connected to the oil inlet of the heating zone, for storing high-temperature thermal oil; the oil inlet of the low-temperature thermal oil tank is connected to the oil outlet of the heat exchange zone, and the oil outlet of the low-temperature thermal oil tank is connected to the oil inlet of the heating zone, for storing low-temperature thermal oil. Those skilled in the art can control the desired temperature by controlling the heat exchange area of ​​the composite thermal oil heat exchange tube, the thermal oil flow rate and other parameters.

[0101] Comparative Example 1 This example provides a method for preparing a hard carbon material, and the steps are basically the same as those in Example 1, except that the treatment of the hemicellulose primary filtrate in steps S1 and S2 is omitted. The specific steps are as follows: 15 g of bamboo powder was treated at 500℃ for 1 h and cooled to room temperature to obtain primary charcoal (primary charcoal yield was 28%). The primary charcoal was further carbonized at 1300℃ for 2 h and cooled to obtain hard carbon material (denoted as: C, hard carbon material yield was 21%).

[0102] Comparative Example 2 This example provides a method for preparing a hard carbon material, and the steps are basically the same as those in Example 1, except that step S1 is omitted, the treatment of the hemicellulose primary filtrate in step S2, and the carbonization treatment at 500°C are performed. The specific steps are as follows: 15 g of bamboo powder was carbonized at 1300℃ for 2 h, and hard carbon material was obtained after cooling (denoted as: DC, the yield of hard carbon material was 22%).

[0103] Test example 1. Use a scanning electron microscope (SEM) to observe the microscopic morphology of the hard carbon materials prepared in Example 1 and Comparative Examples 1-2. Before the test, a small amount of sample powder was dipped on the sample stage with a test paper. In order to improve the conductivity and make the sample surface clearer during observation, Pt was evenly sprayed on the surface for 3 minutes, and the test was performed in the range of 100-1000 times.

[0104] The results are as follows Figure 3 shown.

[0105] After hemicellulose removal and two-step carbonization, AC showed the most dispersed short fiber tube structure and small particle cylindrical structure, and the surface of the hard carbon material was smooth and flat, with almost no obvious mesopores on the outer wall. The change in morphology may be due to the removal of hemicellulose and other substances in the bamboo powder raw material by the alkaline reagent, destroying the original cross-linked structure, resulting in the rupture of the fiber bundle and the release of individual fibers, which is beneficial to the subsequent carbonization process to ensure the smoothness of the fiber bundle, thereby promoting the diffusion and transmission of sodium ions.

[0106] The fiber tubes and flake particles of C after two-step carbonization are more dispersed, and the surface of the material is smooth and flat, with fewer mesopores than DC after one-step carbonization. This may be because the first carbonization treatment helps to form closed pores, thereby reducing the specific surface area of ​​the material, which helps to improve the ICE of the hard carbon negative electrode, and the closed pores provide low voltage platform capacity and improve the reversible capacity of the material.

[0107] 2. X-ray diffraction (XRD) with Cu-Kα radiation at a wavelength of 0.154060 nm was used to characterize the graphite microcrystalline structure of the hard carbon materials obtained in Example 1 and Comparative Examples 1 and 2 in a scanning range of 5° to 90°; a laser micro Raman spectrometer (Raman) with a wavelength of 532 nm and an intensity of 10% was used at 500 cm -1 ~2000 cm -1 The lattice defects and disorder degree were tested in a wide range; the sample was degassed for 10 h in a N2 atmosphere at a degassing temperature of 150°C, and the specific surface area (BET) and mesopore distribution were determined using a N2 adsorption-desorption device.

[0108] The characterization results are as follows Figure 4~Figure 9 shown.

[0109] AC has the highest crystallinity and the degree of graphitization is enhanced, but I D / I G (characterizing defect concentration) is larger, the graphite microcrystalline layer will provide platform capacity and defects will provide tilted capacity, and AC has the smallest specific surface area S BET (19.213 m 2 / g) and pore volume Vpore (0.0205 cm 3 / g), which is beneficial to the improvement of ICE.

[0110] XRD results show that the first carbonization treatment has little effect on the crystal structure of the material and will not affect the degree of graphitization. Raman results show that the first carbonization treatment helps to increase the defect concentration and disorder of the material, which will be beneficial to Na + From the N2 adsorption-desorption isotherm diagram, it can be seen that the first carbonization treatment can effectively reduce the SBET and Vpore of the material and promote the formation of closed micropores, thereby providing Na + Filling the platform area with closed pores provides capacity. The closed pores will not cause a surge in the specific surface area of ​​the material, which helps to inhibit the side reactions between the electrode surface and the electrolyte, thereby improving the ICE of the material.

[0111] 3. Mix hard carbon (AC, C or DC), binder (PVDF), and conductive agent (SuperP) in a mass ratio of 8:1:1 with an appropriate amount of solvent N-methylpyrrolidone (NMP), stir and mix thoroughly to form a uniform slurry, and then apply it on the homogeneous copper foil, dry it in a vacuum drying oven at 80℃ overnight, and cut it into round pole pieces with a cutting machine. Assemble CR2032 button-type sodium ion batteries in a glove box with sodium foil as the counter electrode, 1M NaPF6-DIGLYME as the electrolyte, glass fiber as the diaphragm, and metal sodium sheet as the counter electrode. Use the charge and discharge test system to perform battery charge and discharge tests, analyze the reversible capacity, cycle stability, ICE and rate performance of each battery; use the electrochemical workstation to perform cyclic voltammetry and electrochemical impedance spectroscopy (EIS) tests on the battery.

[0112] Test results such as Figure 10~Figure 16 shown.

[0113] AC has the best sodium storage capacity. At 300 mA g -1 At a current density of 285 mAh g -1 The reversible capacity and ICE of 73.34% are excellent, and the cycle stability and rate performance are also excellent. After 200 cycles, the capacity has basically not decayed. The reversible specific capacities at different rates (0.5 C, 1 C, 2 C, 3 C, 5 C, and 0.5 C) can reach 281.6, 268.2, 254, 234, 201.4, and 260.4 mAh g, respectively. -1 .

[0114] 4. Energy flow and logistics analysis: When the cogeneration system inputs 500 kg d -1 bamboo powder, and finally obtain hard carbon product 115 kg d -1 and hemicellulose products 100 kg d -1 The combined production system works for 8 hours a day with full load, and the total energy required per hour is about 179 MJ h -1 The energy utilization rate of the whole system is 56%. Among them, the energy input into the high temperature carbonization furnace through the solar power supply system is 43 MJ h -1 ; The waste heat from the high temperature hard carbon is transferred to the heat pipe and provides heat energy to the low temperature carbonization furnace to heat 12 MJ h -1 ; Through high temperature hard carbon waste heat (providing 19 MJ h -1 ) supplemented by the calorific value of the volatile matter during carbonization (providing 110 MJ h -1 ) provides heat energy for heating the heat transfer oil, and the heat transfer oil provides heat energy of 2.8 MJ h for the pretreatment device and drying device respectively. -1 and 20 MJ h-1 ; Total energy saving 141 MJ h -1 , accounting for 79% of the required energy, saving a total of 75,000 yuan in electricity costs per year. The environmental heat dissipation losses of the drying system, combustion chamber, high-temperature carbonization furnace, low-temperature carbonization furnace, and pretreatment system are approximately 27 MJ h -1 、12 MJ h -1 、12 MJ h -1 、10MJ h -1 , 2.8 MJ h -1 , a total of about 64 MJ h -1 , accounting for 35% of the total input energy.

[0115] The embodiments of the present invention are described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. An energy-step-driven co-production system of hemicellulose and hard carbon materials, characterized in that: The cogeneration system comprises: A pretreatment module, used for heating a first mixture including a biomass raw material and an alkaline agent, performing a first solid-liquid separation, and obtaining a first solid phase and a first liquid phase; A hemicellulose extraction module, used for sequentially performing a neutralization treatment and an extraction treatment on the first liquid phase, and performing a second solid-liquid separation to obtain the hemicellulose and the second liquid phase; A carbonization module is used to perform carbonization treatment on the first solid phase to obtain the hard carbon material.

2. The cogeneration system according to claim 1, characterized in that: The cogeneration system further includes an energy supply module for collecting volatile matter and thermal energy generated by the carbonization module to provide heat for at least one of the pretreatment module, the hemicellulose extraction module, and the carbonization module.

3. The cogeneration system according to claim 2, characterized in that: The pretreatment module comprises an alkali treatment unit and a first solid-liquid separation unit connected in sequence, wherein the first solid-liquid separation unit has a first liquid phase outlet and a first solid phase outlet; The hemicellulose extraction module comprises a neutralization extraction unit, a second solid-liquid separation unit and a drying unit connected in sequence; the neutralization extraction unit is connected to the first liquid phase outlet; the second solid-liquid separation unit has a second liquid phase outlet and a second solid phase outlet; the drying unit is connected to the second solid phase outlet; The carbonization module comprises a carbonization device and a cooling transpose connected in sequence, and the carbonization device is connected to the first solid phase outlet; The energy supply module includes a heat exchange device and a combustion chamber. The heat exchange device is connected to the cooling device, the combustion chamber and at least one of the alkali treatment unit, the drying unit and the carbonization device; the combustion chamber is connected to the carbonization device.

4. The cogeneration system according to claim 3, characterized in that: The carbonization device comprises a first carbonization unit and a second carbonization unit connected in sequence, and the first carbonization unit is connected to the first solid phase outlet; The cooling device comprises a first cooling unit and a second cooling unit connected in sequence to the second carbonization unit; The combustion chamber is in communication with the first carbonization unit and the second carbonization unit.

5. The cogeneration system according to claim 4, characterized in that: The heat exchange device comprises a first heat transfer device and a second heat transfer device; The first heat transfer device is connected to the second carbonization unit and the first cooling unit at the same time; The second heat transfer device is connected to the second cooling unit, the combustion chamber, and at least one of the alkali treatment unit and the drying unit.

6. The cogeneration system according to claim 5, characterized in that: The first heat transfer device comprises an evaporation part and a condensation part which are connected in sequence, the evaporation part is connected to the first cooling unit, and the condensation part is connected to the first carbonization unit; And / or, the second heat transfer device includes a heating zone and a heat exchange zone connected in sequence, the heat exchange zone is connected to the second cooling unit and the combustion chamber, and the heating zone is connected to at least one of the alkali treatment unit and the drying unit.

7. A method for co-producing hemicellulose and hard carbon materials, characterized in that: The following steps are involved: Heat a first mixture including a biomass raw material and an alkaline agent to react, perform a first solid-liquid separation, and obtain a first solid phase and a first liquid phase; The first liquid phase is sequentially subjected to a neutralization treatment and an extraction treatment, and a second solid-liquid separation is performed to obtain the hemicellulose and the second liquid phase; the first solid phase is carbonized to obtain the hard carbon material.

8. The co-production method according to claim 7, characterized in that: The reaction temperature of the heating reaction is 70°C to 90°C; And / or, the reaction time of the heating reaction is 1 to 2 h; And / or, the pH of the first mixture is 13-14; And / or, the material-liquid ratio of the biomass raw material to the alkaline agent is 1 kg:(10-20) L.

9. The co-production method according to claim 7, characterized in that: The neutralization treatment includes adjusting the pH of the first liquid phase to 2-6; And / or, the extraction treatment comprises: preparing a second mixture of the neutralized first liquid phase and a precipitant, reacting; And / or, the carbonization treatment includes subjecting the first solid phase to a first carbonization treatment at 400° C. to 600° C. and a second carbonization treatment at 1000° C. to 1500° C. in sequence.

10. Use of the co-production system according to any one of claims 1 to 6 or the co-production method according to any one of claims 7 to 9 in the preparation of hemicellulose, hard carbon materials, negative electrodes or secondary batteries.

Citation Information

Patent Citations

  • Municipal sludge pyrolysis treatment system and method

    CN112174469A

  • Biomass two-stage hydrothermal energy production circulating system and method

    CN113214857A

  • Biomass-based hard carbon material as well as preparation method and application thereof

    CN118289733A

  • Carbonizer for carbon material

    JP1994033064A